Outworking of the Second Demographic Transition: National Trends and Regional Patterns of Fertility Change in Poland, and England and Wales, 2002–2012. Issue 6 (21st May 2015) - Walford, Nigel; Kurek, Slawomir
Abstract: One of the main indicators of the second demographic transition (SDT) is the decline of fertility to below the replacement level (2.1 births per woman). The onset of the SDT in Europe spread across Western Europe in the 1960s and subsequently diffused to other parts of the continent. In Eastern Europe, a fall in total fertility rates below the replacement level was recorded at the beginning of the 1990s and was associated by some researchers with the collapse of the communist system and the introduction of a market economy. At present, countries of Eastern Europe record the lowest total fertility rate values (at 1.3–1.4), whereas a fertility recovery has been observed in Northern and Western Europe. Regional, subnational differences in fertility within particular countries associated with uneven dispersal of changes linked with the SDT, especially between urban, suburban, and rural areas, are known to exist but are less well articulated. This paper offers a comparative study of changes in spatial patterns of selected fertility indicators between Poland, and England and Wales, part of the UK, at the beginning of the 21st century. Despite apparent differences at the national level, the paper identifies similarities in the spread of SDT from core to peripheral areas and presents a reduction in the demographic divide between Western and Eastern Europe. Copyright © 2015 John Wiley & Sons, Ltd.